Features of Assessment and Formation of the Aeration Regime of Residential Development on the Sloping Lands of the Russian Arctic - Nina Danilina; Anna Korobeynikova (Buildings, 2022)
The urban development of areas in the Arctic zone of the Russian Federation is a relevant and important task to be tackled by contemporary urban planners. This focus is largely explained by the development of the Northern Sea Route (NSR) and its port cities. Last but not least, to develop these cities means to ensure a comfortable living environment for local residents and visiting specialists. However, given the harsh climate in the Arctic zone of the Russian Federation, this task requires a more elaborate approach. Current building techniques, designed for flatlands with relatively comfortable climates, cannot be applied to this territory without degrading the quality of the living environment. Environmental comfort is influenced by many factors, and one of them is the aeration regime. This study is aimed at researching the aeration regime of built-up areas on the sloping lands of the Arctic zone of the Russian Federation and identifying the features of its formation. The object of this study is a residential development on the sloping lands of the Arctic zone of the Russian Federation. The subject of the study is the external aeration regime at the level of 1.2 m from the ground level of the residential development on the sloping lands of the Arctic zone of the Russian Federation. These parameters were explored, and the aeration regime was assessed using such advanced software packages as QG for the GIS analysis of the area and ANSYS Fluent for the mathematical modeling of the aeration regime. The results of the research are presented in the form of graphs, dependency tables, and petal diagrams visually demonstrating the distribution of discomfortable zones for different morphotypes of development on various slopes most widely spread in the Arctic zone of the Russian Federation. The theoretical research was pilot-tested in the existing residential development area in Murmansk. The results of the study are usable in practice if respective land use documents are drafted for residential areas of settlements in ...